2018
DOI: 10.1371/journal.pone.0191314
|View full text |Cite
|
Sign up to set email alerts
|

Bulk metal concentrations versus total suspended solids in rivers: Time-invariant & catchment-specific relationships

Abstract: Suspended particles in rivers can act as carriers of potentially bioavailable metal species and are thus an emerging area of interest in river system monitoring. The delineation of bulk metals concentrations in river water into dissolved and particulate components is also important for risk assessment. Linear relationships between bulk metal concentrations in water (CW,tot) and total suspended solids (TSS) in water can be used to easily evaluate dissolved (CW, intercept) and particle-bound metal fluxes (CSUS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Geographic differences in the element concentrations in suspended sediment are mostly related to differences in parent material, weathering types and rates, river discharge, organic matter content, and additional natural or anthropogenic sources, including inputs of aerosols and diffuse and point source contaminant inputs, between catchments or river basins (Martin and Meybeck 1979;Savenko 2007). The elemental composition of suspended sediment shows generally less variability in time than in space (Nasrabadi et al 2018;Rügner et al 2019), although the sediment composition may change considerable in response to individual discharge events (e.g. Vale 1990; Schleichert and Keller 1997;Coynel et al 2007;Berner et al 2012;Pulley et al 2016).…”
Section: Responsible Editor: Alexander Koitermentioning
confidence: 99%
“…Geographic differences in the element concentrations in suspended sediment are mostly related to differences in parent material, weathering types and rates, river discharge, organic matter content, and additional natural or anthropogenic sources, including inputs of aerosols and diffuse and point source contaminant inputs, between catchments or river basins (Martin and Meybeck 1979;Savenko 2007). The elemental composition of suspended sediment shows generally less variability in time than in space (Nasrabadi et al 2018;Rügner et al 2019), although the sediment composition may change considerable in response to individual discharge events (e.g. Vale 1990; Schleichert and Keller 1997;Coynel et al 2007;Berner et al 2012;Pulley et al 2016).…”
Section: Responsible Editor: Alexander Koitermentioning
confidence: 99%
“…Previous work has used linear regression approaches for developing water quality proxies such as relationships between turbidity and phosphorus, nitrate, and total suspended solids fluorescence as a proxy for DOC and BOD [29,31,45,46]. In addition, other work has shown that linear relationships can be used to develop proxies with multiple chemical cocktails of metals mostly with turbidity [27,28]. However, there was a gap in the literature for work on proxies of metals using a high-frequency sensor framework suggesting the novelty and importance of this study.…”
Section: Discussionmentioning
confidence: 99%
“…There is a linear relationship between TSS and turbidity where TSS is usually 1-3 times more than the measured turbidity and can aid in the transport of other pollutants (Rügner, et al, 2013). In addition, the linear relationship between TSS and total metal concentrations in rivers is also observed independent of season and events (Nasrabadi et al, 2018). Site 3 is surrounded by residential and commercial areas and it has the highest concentration of oil/grease.…”
Section: Occurrence Of Pollutants In Malihao Rivermentioning
confidence: 97%
“…High concentrations of particulate matter in the river can easily decrease photosynthetic activities and increase in bacteria and nutrient load (BFAR-PHILMINAQ, 2007). Suspended solids found in the rivers can also act as carriers of other potentially harmful pollutants such as heavy metals (Nasrabadi et al, 2018). The presence of oil/grease in water systems of tropical countries is also causing damage to the aquatic environment and this emerging pollutant is recently proposed for inclusion in water quality index parameter for the preservation of marine biota (Eljaiek-Urzola et al, 2019).…”
Section: Introductionmentioning
confidence: 99%